âEfektivitas Desinfektan Benzalkonium klorida-glutaraldehida terhadap Avian Pathogenic Escherichia coli\" - , EMIRA PERMATASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In poultry industry, the use of disinfectants is an important component of biosecurity as an effort to control disease, such as collibacillosis that is caused by Avian Pathogenic Escherichia coli which is the most common disease in poultry. The aim of this research was to evaluate the efficacy of disinfectants benzalkonium chloride-glutaraldehyde in suppressing the growth of Avian Pathogenic Escherichia coli. Benzalkonium chloride-glutaraldehyde has been contacted with the bacteria for 15 minutes then planted it on the nutrient agar media. The result showed that, disinfectant containing active ingredients benzalkonium chloride and glutaraldehyde with minimum composition of 130 ppm benzalkonium chloride and 35 ppm glutaraldehyde was effective in suppressing the growth of Avian Pathogenic Escherichia coli.